2017
DOI: 10.1139/facets-2017-0025
|View full text |Cite|
|
Sign up to set email alerts
|

Honey bee survival is affected by interactions between field-relevant rates of fungicides and insecticides used in apple and blueberry production

Abstract: Certain compounds of low toxicity can increase the susceptibility of an organism to toxic substances; this is known as potentiation. Demethylation inhibiting (DMI) fungicides can potentiate insecticides by impairing the production of detoxification enzymes. As both DMI fungicides and insecticides can be used near or during crop bloom, the combination may be hazardous if exposed to pollinators. Using pesticides used in blueberry or apple production, we conducted laboratory bioassays to test how combinations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…A combination of thiacloprid and triflumizole even led to a 1,141-fold increase in toxicity ( 44 )! Similar results were demonstrated for a combined application of acetamiprid and the SBI fungicide propiconazole ( 131 ). Chronic exposure to these two substances caused synergistic negative effects on the mortality and weight of Asian honeybees ( Apis cerana ) ( 17 ).…”
Section: Combinations Of Neonicotinoids With Sterol Biosynthesis Inhi...supporting
confidence: 78%
See 1 more Smart Citation
“…A combination of thiacloprid and triflumizole even led to a 1,141-fold increase in toxicity ( 44 )! Similar results were demonstrated for a combined application of acetamiprid and the SBI fungicide propiconazole ( 131 ). Chronic exposure to these two substances caused synergistic negative effects on the mortality and weight of Asian honeybees ( Apis cerana ) ( 17 ).…”
Section: Combinations Of Neonicotinoids With Sterol Biosynthesis Inhi...supporting
confidence: 78%
“…Wernecke et al (140) showed that tank mixtures containing the non-SBI fungicides boscalid and dimoxystrobin and the neonicotinoid thiacloprid had no effect on bee toxicity both in laboratory, semifield and field standard assays. Likewise Manning et al (131) showed that the non-SBI fungicides pyraclostrobin and boscalid did not enhance toxicity of the neonicotinoid acetamiprid in honeybees. However, a study of Tsvetkov et al (147) showed that the acute toxicity of the neonicotinoids clothianidin and thiamethoxam was increased when they were co-applied orally in combination with field realistic concentrations of the non-SBI fungicide boscalid.…”
Section: Combinations Of Neonicotinoids and Non-sbi Fungicidesmentioning
confidence: 97%
“…As a sensitive biosensor of environmental changes, the bee colony reacts even to small deviations caused by pollutants. Sublethal effects of plant protection products can be manifested by the changed behaviour of bees when: searching for food, memory disorders, ability to learn, rejection of food, loss of orientation and similar situations [16,24]. The flying worker bees directly affected by insecticide may not have enough energy to return to the bee hive [21].…”
Section: Introductionmentioning
confidence: 99%